Information and Price Dispersion. Theory and Evidence - Dieter Pennerstorfer; Philipp Schmidt-Dengler; Nicolas Schutz; Christoph R. Weiss; Biliana Yontcheva (Austrian Institute of Economic Research (WIFO), 2015)
We examine the relationship between information and price dispersion in the retail gasoline market. We first show that the clearinghouse models in the spirit of Stahl (1989) generate an inverted-U relationship between information and price dispersion. We construct a new measure of information based on precise commuter data from Austria. Regular commuters can freely sample gasoline prices on their commuting route, providing us with spatial variation in the share of informed consumers. We use detailed information on gas station level price to construct various measures of price dispersion. Our empirical estimates of the relationship are in line with the theoretical predictions.
Keywords: 330